IMPROVEMENT QUALITY ELEMENTARY SCHOOL THROUGH THE IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT - Firman; Armaidi; Rahmat Muliana (el-Nizami : Jurnal Manajemen Pendidikan, 2025)
This descriptive qualitative research uses interview, observation, and documentation methods as data collection tools. The sources consisted of principals, teachers, school staff and school committees. The results of this study indicate that SDN Poris Pelawad 3 has implemented TQM well. This is indicated by the Poris Pelawad 3 State Elementary School has adopted the concept of Total Quality Management. The results of the study refer to the theory of Goetsch and Davis, namely: 1. Focus on customers. 2. Obsession with quality. 3. Scientific approach. 4. Long-term commitment. 5. Teamwork, partnerships, and relationships are established and fostered. 6. Continuous system improvement. 7. Education and training. 8. Controlled freedom. 9. Unity of purpose. 10. Involvement and empowerment. The implication is that all school stakeholders are able to implement TQM so that the quality of education at SDN Poris Pelawad 3 in particular and other public elementary schools can be maintained and continue to improve.